2007
DOI: 10.1007/s12010-007-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Chlorophyllase-catalyzed Hydrolysis of Chlorophyll in Monophasic Organic Solvent Media

Abstract: To improve the efficiency of the use of nuclease P1, enzyme immobilization technology was applied using nuclease P1. Characterization of immobilized nuclease P1 on different supports was studied. The results showed that the optimum pH and temperature of nuclease P1 immobilized via different supports were enhanced. The immobilized enzyme was obviously stable when stored for long periods and was reusable. The best results were obtained when nuclease P1 was immobilized on chitosan nanoparticles. The nanoparticles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The specific activity of Chlase was defined as nanomole of substrate (Chl a) hydrolyzed per minute per mg of protein (Arriagada-Strodthoff et al, 2007). The concentration of protein was measured using the method of Lowry et al (1951).…”
Section: Plant Materials Leaves Of Three Representatives Ofmentioning
confidence: 99%
“…The specific activity of Chlase was defined as nanomole of substrate (Chl a) hydrolyzed per minute per mg of protein (Arriagada-Strodthoff et al, 2007). The concentration of protein was measured using the method of Lowry et al (1951).…”
Section: Plant Materials Leaves Of Three Representatives Ofmentioning
confidence: 99%
“…PPAs are used routinely to quantify rates of reactions that release PP i as a byproduct, such as single nucleotide polymorphism (SNP) genotyping reactions (10-12), RNA synthesis by viral RNA-dependent RNA polymerases (13), and aminoacyl-tRNA synthetase activity (14,15). The advantage of PPA-coupled assays is that PPA hydrolyzes PP i to a product (2P i ) which is readily detected by colorimetric assay (16,17).PPAs that operate in a wide variety of organic solvents and salt concentrations are desirable in bioindustry to increase the solubility of hydrophobic substrates, allow for novel synthetic chemistry, alter substrate specificity, ease product recovery, and reduce microbial contamination (18)(19)(20)(21)(22)(23)(24). Biotechnological applications of solvent-tolerant PPAs can be envisioned in the biosynthesis of hydrophobic compounds derived from carbon skeletons such as cholesterol and rubber.…”
mentioning
confidence: 99%
“…PPAs that operate in a wide variety of organic solvents and salt concentrations are desirable in bioindustry to increase the solubility of hydrophobic substrates, allow for novel synthetic chemistry, alter substrate specificity, ease product recovery, and reduce microbial contamination (18)(19)(20)(21)(22)(23)(24). Biotechnological applications of solvent-tolerant PPAs can be envisioned in the biosynthesis of hydrophobic compounds derived from carbon skeletons such as cholesterol and rubber.…”
mentioning
confidence: 99%
“…If the reaction temperature was continuously raised to 70 and 80 • C, the yield of pheophorbide was not parallel to lower temperatures, which suggested some degradation process occurred at these high temperatures. Previous studies have found that the optimum reaction temperature for the enzymatic activity of chlorophyllase and pheophytinase is around 35 to 50 • C (Arriagada-Strodthoff et al, 2007;Guyer et al, 2018). So, high temperatures will affect enzyme activity, and thus, reduce the yield of pheophorbides.…”
Section: Effect Of Temperature and Time On The Enzymatic Reaction Of ...mentioning
confidence: 99%